Terahertz spectra of proteinuria and non-proteinuria - Xue, Zhenrui; Mao, Ping; Peng, Ping; Yan, Shihan; Zang, Ziyi; Yao, Chunyan (Frontiers in Bioengineering and Biotechnology, 2023)
In clinical practice, proteinuria detection is of great significance in the diagnosis of kidney diseases. Dipstick analysis is used in most outpatient settings to semi-quantitatively measure the urine protein concentration. However, this method has limitations for protein detection, and alkaline urine or hematuria will cause false positive results. Recently, terahertz time-domain spectroscopy (THz-TDS) with strong hydrogen bonding sensitivity has been proven to be able to distinguish different types of biological solutions, which means that protein molecules in urine may have different THz spectral characteristics. In this study, we performed a preliminary clinical study investigating the terahertz spectra of 20 fresh urine samples (non-proteinuria and proteinuria). The results showed that the concentration of urine protein was positively correlated with the absorption of THz spectra at 0.5–1.2 THz. At 1.0 THz, the pH values (6, 7, 8, and 9) had no significant effect on the THz absorption spectra of urine proteins. The terahertz absorption of proteins with a high molecular weight (albumin) was greater than that of proteins with a low molecular weight (β2-microglobulin) at the same concentration. Overall, THz-TDS spectroscopy for the qualitative detection of proteinuria is not affected by pH and has the potential to discriminate between albumin and β2-microglobulin in urine.